SOSIALISASI DAN EDUKASI DAGUSIBU (DAPAT, GUNAKAN, SIMPAN, BUANG) OBAT YANG TEPAT DI SMP NEGERI 5 KENDARI - Aspadiah, Vica; Hasnawati, Hasnawati; Nauli, Agnes; Ahmad, Murliyana; Hanija, Nur; Putri, Riski Melani; Tolohuly, Syahril Musafir Ratu; Akib, Nur Illiyin; Muliadi, Rahmat (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
DAGUSIBU is a Family Movement Program focused on Drug Awareness, aimed at increasing public knowledge and awareness regarding the proper and responsible use of medications. This outreach effort is intended to educate the community on how to implement safe and appropriate drug usage based on the principles of the DAGUSIBU concept. The method applied involves interactive lectures combined with the distribution of questionnaires in the form of pre-tests and post-tests to assess participants’ understanding. The outcomes revealed that most participants showed improved knowledge and comprehension of drug use, as evidenced by the difference in their pre- and post-test results. They became more capable of distinguishing between prescription and non-prescription drugs, identifying legal sources for obtaining medications, and recognizing the importance of proper storage and disposal of pharmaceutical products. Therefore, DAGUSIBU serves as an effective and proactive strategy to promote family health and prevent the misuse of drugs within the community